Особливості професійної підготовки фахівців з інформаційних технологій в університетах США - Кулєшов, Сергій Олександрович; Кулешов, Сергей Александрович; Kulieshov, Serhii (My University, 2019)
UK:У статті розглядаються особливості системи професійної підготовки майбутніх бакалаврів з інформаційних технологій в університетах США. Проведено аналіз документальних і наукових джерел щодо специфіки підготовки ІТ-фахівців в університетах США. Представлені результати рейтингу QS World University Rankings за 2019 р. у сфері «Комп’ютерні науки та інформаційні технології», у якому представлені кращі університети світу, серед яких американські займають перші місця. Цим пояснюється актуальність дослідження та інтерес саме до професійної підготовки майбутніх фахівців з інформаційних технологій в університетах США. Розглянуто основні рекомендації щодо планування навчальних програм: з комп’ютерної інженерії (Curriculum Guidelines for Undergraduate Degree Programs in Computer Engineering, 2016), з комп’ютерних наук (Curriculum Guidelines for Undergraduate Programs in Computer Science, 2013), з кібербезпеки (Curriculum Guidelines for Post-Secondary Degree Programs in Cybersecurity, 2017), з інформаційних систем (Curriculum Guidelines for Undergraduate Degree Programs in Information Systems, 2016), з інформаційних технологій (Curriculum Guidelines for Baccalaureate Degree Programs in Information Technology, 2017), з інженерії програмного забезпечення (Curriculum Guidelines for Undergraduate Degree Programs in Software Engineering, 2014). Вони розробляються Асоціацією обчислювальної техніки (англ. Association for Computing Machinery, ACM) у співробітництві з комп’ютерним товариством IEEE (IEEE Computer Society) та іншими провідними професійними та науковими комп’ютерними товариствами. Представлено та пояснено схему розрахунку кредитів системи вищої освіти США. Проаналізовані відмінності між рейтинговими системами, які розроблені на основі семестрового та квартального календарів. Зроблені висновки дослідження, які полягають у визначенні та висвітленні особливостей організації освітнього процесу в університетах США. Встановлено перспективні напрямки для подальших досліджень, що дозволить визначити провідні тенденції розвитку системи ІТ-освіти у контексті трансформацій світової системи освіти. EN: The article deals with the peculiarities of the training system of future bachelors in information technology at US universities. The analysis of documentary and scientific sources concerning the specifics of IT specialist training at US universities has been conducted. The results of QS World University Rankings 2019 in the field of Computer Science and Information Technology, which presented the best universities in the world, among which the US universities ranked first, has been introduced. This fact explains the relevance of the research and the interest in the training of future IT professionals at US universities. The main recommendations for curriculum planning are Curriculum Guidelines for Undergraduate Degree Programs in Computer Engineering, 2016, Curriculum Guidelines for Undergraduate Programs in Computer Science, 2013, Curriculum Guidelines for Post-Secondary Degree Programs in Cybersecurity, 2017, Curriculum Guidelines for Undergraduate Degree Programs in Information Systems, 2016, Curriculum Guidelines for Baccalaureate Degree Programs in Information Technology, 2017, Curriculum Guidelines for Undergraduate Degree Programs in Software Engineering, 2014. They have been developed by the Association for Computing Machinery (ACM), in collaboration with the IEEE Computer Society and other leading professional and scientific computer societies. The scheme of credit calculation in the higher education system of the USA has been presented and explained. The differences between rating systems developed on the basis of semester and quarterly calendars have been analyzed. The conclusions of the research, which consist in determining and highlighting the peculiarities of the organization of theeducational process at US universities, are made. Perspective directions for further research have been set, which will determine the promising tendencies of the IT education system development in the context of the world education system transformations.
Features of professional training of information technology specialists at US universities
Keywords: професійна підготовка; освітній процес; інформаційні технології; університети США; бакалавр з інформаційних технологій; professional training; educational process; information technologies; US universities; bachelor in information technology